2009
DOI: 10.1007/s10162-009-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Cell Characteristics in Long-deafened Aged Mouse Ears

Abstract: Significant sensory hair cell loss leads to irreversible hearing and balance deficits in humans and other mammals. Future therapeutic strategies to repair damaged mammalian auditory epithelium may involve inserting stem cells into the damaged epithelium, inducing non-sensory cells remaining in the epithelium to transdifferentiate into replacement hair cells via gene therapy, or applying growth factors. Little is currently known regarding the status and characteristics of the non-sensory cells that remain in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 73 publications
6
50
0
Order By: Relevance
“…3G and H). Sox2 expression was shown in the nuclei of all subtypes of supporting cells in adult mouse cochleae (Oesterle and Campbell, 2009). Our findings showed a similar pattern ( Fig.…”
Section: Preservation Of Immunogenicitymentioning
confidence: 96%
“…3G and H). Sox2 expression was shown in the nuclei of all subtypes of supporting cells in adult mouse cochleae (Oesterle and Campbell, 2009). Our findings showed a similar pattern ( Fig.…”
Section: Preservation Of Immunogenicitymentioning
confidence: 96%
“…However, in long-deafened aged animal models where the organ of Corti is severely damaged by aminoglycosides, differentiated support cells can be maintained for long periods of time in remnant organ of Corti in the absence of hair cells (Sugawara et al, 2005; Oesterle et al, 2009). The remnant organ of Corti has also been called the “repaired organ of Corti” or the “repaired columnar epithelium” (Taylor et al, 2012), and the latter term will be used here.…”
Section: Support Cell Phenotype Changes After Damagementioning
confidence: 99%
“…Light and electron microscopy studies have shown that the distinctive specializations of pillar and Deiters’ cells, such as the prominent intracellular bundles of closely packed microtubules that are acquired during late states of organ of Corti maturation (Forge et al, 1997; Souter et al, 1997), persist in the repaired organ when columnar support cells remain (Oesterle et al, 2008, Oesterle and Campbell, 2009; Taylor et al, 2012). Further, histochemical studies show that acetylated tubulin, a component of the distinctive intracellular bundles (Tannenbaum and Slepecky, 1997; Saha and Slepecky, 2000) is retained (Oesterle and Campbell, 2009; Taylor et al, 2012). Studies of KCC4, a plasma membrane protein involved in potassium uptake that is upregulated during the latter stages of organ of Corti maturation in inner border and Deiters’ cells (Boettger et al, 2002), indicate KCC4 is retained in repaired organ of Corti when columnar support cells remain despite massive or complete hair cell loss (Taylor et al, 2012).…”
Section: Support Cell Phenotype Changes After Damagementioning
confidence: 99%
See 2 more Smart Citations